SO2 modeling in Izmit Gulf, Turkey during the winter of 1997: 3 cases - TAYANÇ, METE (SPRINGER, 2007)
In this study, SO2 dispersion over Izmit Gulf is simulated by California Puff (CALPUFF) model for three air pollution cases, which occurred on January 28, February 12, and February 26, 1997. These days are generally characterized by dominant high-pressure systems - pressure values reaching 1032 mb, low wind speeds and sometimes calm conditions, and low temperatures with a minimum of 0 degrees C. Hourly simulations during those critical cases were carried out and results revealed very high concentrations of SO2 transported to the downwind regions of Tupras and Gebze, and values sometimes exceeded 1,000 mu g/m(3). Nighttime and morning simulations associated with inversion produced considerably higher values of SO2 than the afternoon simulations associated with breeze. Model verification was conducted by comparing the measured daily average values of eight stations with the model predicted values at the same receptor points. Results showed that the model well predicted the values at station Gebze in all three cases. The model sometimes underestimated and sometimes overestimated the concentrations at other receptor stations.
Keywords: air pollution modeling; Izmit Gulf region; CALMET; CALPUFF; POWER-PLANT EMISSIONS; AIR-POLLUTION; CALPUFF; IMPACTS; MEXICO